2021
DOI: 10.3390/cancers13061425
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial HDR Brachytherapy in the Treatment of Non-Melanocytic Skin Cancers around the Eye

Abstract: Background: Eyelid tumors are rare skin cancers, the most common of which is basal cell carcinoma characterized primarily by local growth. In addition to surgery, radiotherapy is among the basic methods of treatment. External beam radiotherapy is associated with the risk of complications within ocular structures, especially the lens. In the case of interstitial brachytherapy, it is possible to administer a high dose to the clinical target volume (CTV), while reducing it in the most sensitive structures. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…One the largest and most recent articles is by Cisek et al, who confirmed the effectiveness of the exclusive periorbital interstitial IRT, with excellent results in terms of local control as well as functional and cosmetic outcomes in their series including 28 patients [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…One the largest and most recent articles is by Cisek et al, who confirmed the effectiveness of the exclusive periorbital interstitial IRT, with excellent results in terms of local control as well as functional and cosmetic outcomes in their series including 28 patients [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Supreme precision is especially required in facial region. Cisek et al reported treatment outcomes of 28 patients with eyelid NMSCs treated with HDR BT 36 . One local recurrence was reported with median follow up 22 months.…”
Section: Methodsmentioning
confidence: 99%
“…Patients selected for BT usually are disqualified from operation because of age, tumor location or high tumor volume. Patel et al directly compared BT to Mohs microsurgery in a matched pair cohort study 36 . One hundred and eighty‐eight patients received BT, 181 patients Mohs surgery.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations